Branched-chain amino acids for growing cattle limit-fed diets based on soybean hulls - Löest, C.A.; Lambert, B.D.; Trater, A.M.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study evaluated the effects of branched-chain amino acids on nitrogen retention and plasma branched-chain amino acid concentrations. Five ruminally cannulated Holstein steers (387 lb) were used in a 5 × 5 Latin square. Steers were limit-fed soybean hull-based diets twice daily (7.5 lb/day, as fed basis). Energy in the form of acetate (400 grams/day) was continuously infused into the rumen. Treatments were continuous abomasal infusions of 1) 115 grams/day of a mixture of 10 amino acids, 2) 10 amino acid mix with leucine removed, 3) 10 amino acid mix with isoleucine removed, 4) 10 amino acid mix with valine removed, and 5) 10 amino acid mix with all three branched-chain amino acids removed. Nitrogen retention decreased (P<0.06) in response to removal of leucine, valine, or all three branched-chain amino acids. Changes in nitrogen balance of growing cattle limit-fed soybean hull-based diets demonstrate limitations in the basal supply of leucine and valine, but not isoleucine.
Keywords: Beef; Leucine; Isoleucine; Valine; Steers